Værkfortegnelser (Nielsen, Hartmann og Scheibe) Review essay - Holme, Thomas (Danish Yearbook of Musicology, 2018)
Review of: Catalogue of Carl Nielsen’s Works, ed. Niels Bo Foltmann, Axel Teich Geertinger, Peter Hauge, Niels Krabbe, Bjarke Moe and Elly Bruunshuus Petersen. Danish Humanist Texts and Studies, 53. Copenhagen: The Royal Library / Museum Tusculanum Press, 2016. J.P.E. Hartmann. Thematic-bibliographic Catalogue of his Works, ed. Inger Sørensen. Danish Humanist Texts and Studies, 56. Copenhagen: The Royal Library / Museum Tusculanum Press, 2017. Johann Adolph Scheibe. A Catalogue of His Works, ed. Peter Hauge. Danish Humanist Texts and Studies, 58. Copenhagen: The Royal Library / Museum Tusculanum Press, 2017.